Decreased peroxidase activity of glycated hemoglobin inversely correlated with levels of glycated hemoglobin in type 2 diabetes patients - Pinaki Saha; Pradipta Ghosh; Santanu Sen; Usashi Biswas Bose; Shreya Mandal; Indira Bhaskar Biswas; Utpal Kumar Biswas (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Diabetes mellitus is a metabolic disorder with diverse etiological factors. Imbalances between oxidative stress and antioxidant defences play critical roles in the pathogenesis and progression of diabetes. peroxidase, an antioxidant enzyme similar to superoxide dismutase and catalase, is involved in the aetiology and progression of diabetes. This study aimed to elucidate the relationship between the peroxidase activity of hemoglobin and glycated hemoglobin with fasting blood glucose levels in patients with type 2 diabetes mellitus. Sixty-four patients with type-2 diabetes mellitus and an equal number of healthy controls were recruited for the study. Peroxidase activity of hemoglobin and glycated hemoglobin was assayed using L. Goth's method for serum catalase assay, with further modification and standardization. Peroxidase activity of hemoglobin was significantly reduced (P<0.0001) in patients with type 2 diabetes compared to healthy controls, as was peroxidase activity of glycated hemoglobin (P< 0.001). In both patients and controls, peroxidase activity of glycated hemoglobin was significantly higher than normal hemoglobin. In patients with type 2 diabetes, glycated hemoglobin showed a significant negative correlation (r=- 0.308, P= 0.013) with its peroxidase activity, indicating increased activity is associated with poorer glycemic control. Furthermore, peroxidase activiy of normal hemoglobin positively correlated with peroxidase activity of glycated hemoglobin (mainly HbA1c )(r= 0.305, P=0.014). Peroxidase activity of glycated hemoglobin increases with glycated hemoglobin levels, indicating deteriorating glycaemic control in patients with type 2 diabetes.